2022
DOI: 10.3389/fnins.2022.951964
|View full text |Cite
|
Sign up to set email alerts
|

Long-term morphological and functional dynamics of human stem cell-derived neuronal networks on high-density micro-electrode arrays

Abstract: Comprehensive electrophysiological characterizations of human induced pluripotent stem cell (hiPSC)-derived neuronal networks are essential to determine to what extent these in vitro models recapitulate the functional features of in vivo neuronal circuits. High-density micro-electrode arrays (HD-MEAs) offer non-invasive recording with the best spatial and temporal resolution possible to date. For 3 months, we tracked the morphology and activity features of developing networks derived from a transgenic hiPSC li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 109 publications
2
18
0
Order By: Relevance
“…iNGN-derived neurons require an additional time for functional maturation ( Lam et al, 2017 ; Schmieder et al, 2022 ). During this maturation phase a connected network of neurons develops, network bursts arise, and a GABAergic system evolves, resembling human brain development ( Habibey et al, 2022 ). In the first 4 days of induction, an increase in the expression of glutamatergic genes was measured ( Busskamp et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…iNGN-derived neurons require an additional time for functional maturation ( Lam et al, 2017 ; Schmieder et al, 2022 ). During this maturation phase a connected network of neurons develops, network bursts arise, and a GABAergic system evolves, resembling human brain development ( Habibey et al, 2022 ). In the first 4 days of induction, an increase in the expression of glutamatergic genes was measured ( Busskamp et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…At 30 days post induction (dpi), about 2.3% of neurons have been shown to be GABAergic (Lu et al, 2019). This fraction increases over time and recent results suggest an increase in the number of inhibitory neurons after 60 dpi (Habibey et al, 2022). More detailed functional characterization of long-term development of iNGN networks has shown that the majority of iNGN neurons have functional synapses after 21 days and functional AMPA/KA receptors are present in iNGN neurons as confirmed by immunohistochemistry and patch-clamp experiments (Lam et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro network function is mainly studied multi-electrode arrays (MEAs) electrophysiology and optical tools like calcium imaging and optogenetics [11,14,15,22,23]. Non-invasive in vitro electrophysiology tools for multi-site long-term recordings, including transparent MEAs and high-density MEAs, are commercially available [13,22,[24][25][26][27]. They have been applied for mapping the functional connectivity patterns in randomly connected 2D neuronal networks [14,26,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, random networks do not recapitulate the modular structure of the brain circuits [28]. In addition, in vitro network structure undertakes changes by culture age due to the shifts in the position of the neuronal cell body and axonal branches [14,21,27]. It means that a specific electrode does not necessarily record from same neurons or part of the circuit over weeks and months of network development [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation